Activity of mitogen‐activated protein kinases in the esophageal epithelium of patients with Barrett's esophagus. Issue 6 (27th May 2014) - Chwiesko, A.; Baniukiewicz, A.; Semeniuk, J.; Kaczmarski, M.; Wasielica‐Berger, J.; Milewski, R.; Dabrowski, A.
Summary Barrett's esophagus (BE), a complication of gastroesophageal reflux disease, is associated with an increased risk of esophageal cancer. Mitogen‐activated protein kinases may play an important role in the pathogenesis of this process. We aimed to evaluate mitogen‐activated protein kinases activity in esophageal mucosa of patients with BE and find possible relationship between reflux type and BE. Twenty‐four patients (mean age: 59 years) with gastroesophageal reflux disease symptoms and endoscopically suspected esophageal metaplasia (ESEM) were prospectively enrolled for testing by a multichannel intraluminal impedance monitoring along with a Bilitec 2000. Endoscopic biopsies were taken from methylene blue‐positive pit patterns (sites suggesting specialized intestinal metaplasia [SIM]), from 2 cm above the Z‐line and from cardial parts of the stomach. The biopsies were analyzed for extracellular signal‐regulated kinase (ERK), c‐Jun N‐terminal kinase (JNK), p38 activity by Western blot. Seventeen ESEMs had histologically proven metaplasia: eight patients had SIM and nine had gastric‐type epithelia (GE). Biliary reflux was more evident in SIM (P = 0.019) but not in GE (P = 0.019); non‐biliary reflux was typical for GE (P = 0.005) but not for SIM (P = 0.04). Strong activations of ERK and p38 were found predominantly in SIM, but not in normal esophageal mucosa (NE) (P = 0.01 and P < 0.001 respectively). Strong signals for active JNK and p38 were detected in GE, but not in NE (P = 0.006 and P = 0.02 respectively). ERK activity was significantly higher than p38 activity in ESEM patients only with GE (P = 0.02). The strong activation of ERK, but not JNK is indicative of SIM. The presence of bile in gastroesophageal refluxate is predisposing to SIM, but not to GE in esophageal mucosa.